Using Collaborative Technologies for Chatbots’ Creation, Development and Delivery - Gallegos, Luciano (Anais Estendidos do Simpósio Brasileiro de Sistemas Colaborativos (SBSC), 2021)
The COVID-19 pandemic suddenly moved thousands for working remotely and since then had speeded up the use of collaborative technologies. In this industry report paper, we describe our 1-year experience using these collaborative technologies for the creation, development and delivery of chatbots, which are system used to conduct online conversation via text or speech, replacing a live human agent. This industry report experience gathered government professional, academic professors, researchers, graduate and undergraduate students, where 2 chatbots were successfully delivered.